Technology review and thermodynamic performance study of a biogas-fed micro humid air turbine. (September 2019) - MosayebNezhad, M.; Mehr, A.S.; Lanzini, A.; Misul, D.; Santarelli, M.
Abstract: Biogas is a proven and valuable energy source today for the combined production of heat and electricity (CHP). One of the most reliable and efficient technologies for the CHP application using biogas is represented by microturbine (MT). This prime mover not only shows a very flexible behavior towards change in the fuel composition, but it also sticks out for its reliability, small size, and low weight. Moreover, micro humid air turbine (mHAT) cycle, which is still under development, provides a relatively simple and inexpensive solution to increasing the power output of the microturbines. In this paper, the thermodynamic model of a novel CHP system based on a 500 kW micro humid air turbine (mHAT) in a wastewater treatment plant (WWTP) is presented and discussed. Furthermore, some considerations regarding an appropriate biogas treatment system and heat recovery module are discussed. The results presented in this paper show how the proposed biogas-fed plant can achieve an electrical efficiency of 46.6% together with a CHP efficiency of 81.2%. The impact of integration with WWTPs is beneficial where both biogas and required water for inlet air humidification are available. Highlights: A review on microturbine technology and commercially available products is presented. A model is created for thermodynamic performance assessment of the proposed 500 kW biogas fed mHAT system. Key parameters affecting the plant performance are discussed. BOP equipment for the proposed system installation in a WWTP is described.